Regulatory Capacity Review : East African Community - International Finance Corporation (Washington, DC, 2017)
The regulatory capacity review of the East African Community (EAC) focuses on the capacities of the EAC institutional framework to develop, implement, and sustain the efficient, transparent, and market-based regulatory system that is needed to achieve the economic benefits of the EAC common market. This report argues that the EAC institutions will be successful in implementing the common market only if they safeguard the quality of regulatory practices. This is a highly pragmatic and operational agenda. Quality principles can be applied only if they are defined and institutionalized into the machinery of policy making. The idea is that, just as fiscal management can increase social welfare by better allocating resources, so can regulatory governance.